Identification of unknown operating system type of Internet of Things terminal device based on RIPPER - Shichang Xuan; Dapeng Man; Wu Yang; Wei Wang; Jiashuai Zhao; Miao Yu (International Journal of Distributed Sensor Networks)
Due to the vast popularity of sensors, cloud computing, mobile computing, and intelligent devices, the Internet of Things has seen tremendous growth in recent years. Operating system type recognition is the core technology of network security assessment. Due to inherit security problems of Internet of Things such as the situation of risk and threat of information, the operating system recognition seeks research attention for Internet of Things network security. In view of the current identification method of active operating system, it is prone to be detected by intrusion detection system. The operating system identification technology based on transmission control protocol/Internet protocol fingerprint library is more complicated than to distinguish the operating system types of unknown fingerprints. In this work, a passive operating system identification method based on RIPPER model is proposed. Also, it is compared with the existing support vector machine and C45 decision tree classification algorithms. Experiments reveal that RIPPER-based algorithm has better recognition accuracy and recognition efficiency.